2019
DOI: 10.14740/jem572
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Clinical and Laboratory Findings Among Graves’ Disease, Painless Thyroiditis and Subacute Thyroiditis Patients With Hyperthyroidism

Abstract: Background: Graves' disease, painless thyroiditis and subacute thyroiditis are important in the differential diagnosis for hyperthyroidism in Japan. Methods: We retrospectively picked up patients who had been diagnosed as having hyperthyroidism, at National Center for Global Health and Medicine Kohnodai Hospital, between January 2010 and October 2018. According to the guideline for diagnosis of Graves' disease, painless thyroiditis and subacute thyroiditis presented by the Japan Thyroid Association, we diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…In the guideline for Graves' disease, the fT3/fT4 ratio is helpful to exclude painless thyroiditis. Differences in clinical, endocrinological, immunological and biochemical findings and diagnostic imaging among Graves' disease, subacute thyroiditis and painless thyroiditis were shown in Table 2 [14]. As newly obtained findings, levels of fT3 and fT4 and the fT3/fT4 ratio were higher in the order of Graves' disease, subacute thyroiditis and painless thyroiditis.…”
Section: Differential Diagnosis Of Thyrotoxicosissupporting
confidence: 52%
See 1 more Smart Citation
“…In the guideline for Graves' disease, the fT3/fT4 ratio is helpful to exclude painless thyroiditis. Differences in clinical, endocrinological, immunological and biochemical findings and diagnostic imaging among Graves' disease, subacute thyroiditis and painless thyroiditis were shown in Table 2 [14]. As newly obtained findings, levels of fT3 and fT4 and the fT3/fT4 ratio were higher in the order of Graves' disease, subacute thyroiditis and painless thyroiditis.…”
Section: Differential Diagnosis Of Thyrotoxicosissupporting
confidence: 52%
“…In Japan, Graves' disease, painless thyroiditis and subacute thyroiditis are important in the differential diagnosis for thyrotoxicosis. We retrospectively picked up patients who had been diagnosed as having Graves' disease, painless thyroiditis and subacute thyroiditis who showed thyrotoxicosis, at National Center for Global Health and Medicine Kohnodai Hospital, between January 2010 and October 2018 [14]. The guideline for diagnosis of painless thyroiditis by Japan Thyroid Association includes thyrotoxicosis without pain of the thyroid gland and spontaneous improvement of thyrotoxicosis, elevation of serum fT4, suppression of TSH and negative for TRAb.…”
Section: Differential Diagnosis Of Thyrotoxicosismentioning
confidence: 99%
“…A third-generation assay for circulating antibodies to the thyrotropin receptor (TRAb) has been developed, offering a sensitivity of 95 and 100% specificity, but mild GD patients might be TRAb negative (12). Serum fT 3 levels in GD patients were significantly higher than in patients with painless thyroiditis and SAT (13). The free fT 3 /fT 4 of patients with painless thyroiditis overlapped with those of patients with GD.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies analyzed thyroid function test results according to age, sex, and etiology [ 9 , 10 ]. It has been suggested that T3, T4, and ratio of T3 to total thyroxine (T4) are high during early-onset Graves’ disease [ 11 , 12 ], which is characterized by an increase in thyroid hormone production [ 13 ].…”
Section: Discussionmentioning
confidence: 99%